Serial disparity in the carnivoran backbone unveil a complex adaptive role in metameric evolution. - Figueirido-Castillo, Francisco Borja; Martín-Serra, Alberto; Pérez-Ramos, Alejandro; Velasco, David; Pastor, Francisco J.; Benson, Roger J. (My University, 2021)
Organisms comprise multiple interacting parts, but few quantitative studies have analysed multi-element systems, limiting understanding of phenotypic evolution. We investigate how disparity of vertebral morphology varies along the axial column of mammalian carnivores — a chain of 27 subunits — and the extent to which morphological variation have been structured by evolutionary constraints and locomotory adaptation. We find that lumbars and posterior thoracics exhibit high individual disparity but low serial differentiation. They are pervasively recruited into locomotory functions and exhibit relaxed evolutionary constraint. More anterior vertebrae also show signals of locomotory adaptation, but nevertheless have low individual disparity and constrained patterns of evolution, characterised by low-dimensional shape changes. Our findings demonstrate the importance of the thoracolumbar region as an innovation enabling evolutionary versatility of mammalian locomotion. Moreover, they underscore the complexity of phenotypic macroevolution of multi-element systems and that the strength of ecomorphological signal does not have a predictable influence on macroevolutionary outcomes
Keywords: Columna vertebral - Evolución; Carnívoros; Backbone; Disparity; Carnivorans; Geometric Morphometrics; Constraints